The Traditional Game of Throwing Sandals in Learning Narrative Writing for Elementary School Students - Sri Wulan Anggraeni; Rahman; Istikhoroh Nurzaman; Asep Nurhuda; Yayan Alpian (Jurnal Ilmiah Sekolah Dasar, 2023)
Writing is a very important language skill in school. However, there are still many students who need help with writing. This study analyzes learning to write narratives by applying the traditional game of throwing sandals. The research method used is descriptive qualitative. The research subjects were 18 elementary school students. Data were collected through observation, questionnaires, and story-writing skill tests; After that, the data was evaluated using data reduction, data display, and verification methods. The results showed that learning to write narratives using the traditional game "Throw Sandals" impacted student activity, namely an average score of 3.7 and above, and students were enthusiastic about learning. Judging from the student's response to the traditional game of throwing sandals, an average score of 3.8 was obtained, and the average score for students' narrative writing ability was 82.4. These findings conclude that learning to write narratives using the traditional sandal-throwing game method can be successful, and students can easily express ideas from the experience gained. The traditional game of throwing sandals makes children interact with each other and can help shape and maintain a child's social spirit. Traditional games can encourage students' thinking to be more creative and increase self-confidence. Based on the research results, it can have implications for the quality of learning and the introduction of Indonesian culture to students.